Evaluation of Integrated Library Management Software (ILMS) Koha and e-Granthalaya: A Comparative Analysis - Suman, Anubhaw Kumar; Kumar, Ravi; Paul, Debashish Pandit (Access: An International Journal of Nepal Library Association, 2024)
The present study compares the features, modules and technical aspects of two common and popular Integrated Library Management System (ILMS) Software, i.e. Koha and e-Granthalaya. The study aims to find the common and special features among both software and f ind the most suitable software for particular libraries. A checklist comprising several parameters like technical specifications and requirements, functional modules, general features, specific features, module integration, and many more were tabulated for comparison. The study found that Koha has more specific features than e-Granthalaya. Some modules in Koha are superior to those in e-Granthalaya, like the acquisition module, which is simpler and more user-friendly, and Koha has an advanced OPAC system. Although, e-Granthalaya outperforms Koha regarding cataloguing, circulation, and serial management. The study also recommends further improvement in e-Granthalaya. Study also revealed the literature and research gap on e-Granthalaya which open the scope of future study on e-Granthalaya software and its comparison with other software.